Os dados estão lançados na moda: do cool hunting à datificação, uma análise de como o comportamento social vira produto para redes fast fashion como a Shein - Tremarin, Alexandre Camilo (Universidade do Vale do Rio dos Sinos, 2022)
With the advancement of technology and the increasing shift from a media society to one influenced by mediatization, the social field of fashion was forced to transform itself. In this context, this analysis investigates the influence of the public in the creation of fashion products, since their digital interactions with brands, investigates the market operations and discursive logics of the Chinese fast fashion brand Shein, and relates it to others in the same segment. It intensifies a market dispute and opens wide discussion about piracy, sustainability, ethics, and use of data. The hypotheses are that datification reconfigures the field of fashion, fashion largely appropriates culture, and there is a circular relationship between fashion, culture and data. The main objective is to investigate the transformations of the fashion market from the changes of the media, especially considering the datitification platforms, managed by algorithms. Among the specific objectives are: to investigate whether the success of brands is in fact achieved to a greater degree when the consumer plays an important role in the creation process (PUCHASKI, 2008); seek analogies and homologies between the empirical cases under analysis; inferring from other experiments in fashion, in a comparative way; understand individualism in fashion and connect with the fashion market's own desires and offers. The research design comprises a set of procedures and techniques with a qualitative approach, in which the use of Grounded Theory was defined (GLASSER & STRAUSS, 1967), with emphasis on the Straussian current (CORBIN & STRAUSS, 2008). The main finding is that the media circulation on digital social media networks of Shein provides an amplification of its economic benefits. At the same time, it takes advantage of the promotional activity carried out by the media collaboration of its own consumers and incorporates it into the brand's advertising circulation.
Keywords: Moda; Tendência; Midiatização; Datificação; Shein; Fashion; Trend; Mediatization; Datification; ACCNPQ::Ciências Sociais Aplicadas::Comunicação